APA SAJA FAKTOR - FAKTOR YANG MEMPENGARUHI HARGA SAHAM - Fadila, Anisa Nur; Nuswandari, Cahyani (LPPM Universitas Sains dan Teknologi Komputer, 2022)
The share price is the value determined by the strength of the offer to buy and sell shares in a certain market mechanism and is the selling price from one investor to another. Stock price is one indicator of company management. Success in generating profits will provide satisfaction for rational investors. This study aims to provide empirical evidence of the effect of the variable eps, profitability ratios, liquidity ratios, and solvency ratios on stock prices in manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange for 3 periods, namely 2018-2020. Based on the results of the study, it is proven that: Earning Per Share (EPS) has a significant effect on stock prices. Profitability Ratio (ROE) has no significant effect on stock prices. Liquidity Ratio (CR) has no significant effect on stock prices. Solvency Ratio (DER) has no significant effect on stock prices.